EVALUASI PROSES BELAJAR MENGAJAR BIOLOGI PADA PEMBELAJARAN TATAP MUKA TERBATAS DI KELAS XI IPA SMAN 1 PANGKALAN KURAS - Rahmah Mailani Areta; Fitra Suzanti; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Covid 19 has had many impacts on various fields, one of which is the field of education. SMAN 1 Pangkalan Kuras began to apply PTM-Limited in September 2021. In implementing PTM-Limited, several problems were found that students complained about, such as assessments that were charged with assignments and a decrease in understanding of the material.The purpose of this study was to determine the results of the evaluation of the biology teaching and learning process in limited Face-to-face learning in grade XI science at SMAN 1 Pkl. Kuras. The samples of this study were students and teachers of grade XI science at SMAN 1 Pkl.kuras. The instruments to collect the data were questionnaires and interviews. To analyze the data used descriptive quantitative analysis techniques and percentages. After analyzing the data, it can be concluded: the learning planning aspect is categorized as good with a percentage of 71.72%, the learning implementation aspect is categorized as good with a percentage of 72.91%, and learning assessment aspect is categorized as good with a percentage of 64.13%. So overall, the total average percentage of the evaluation of the teaching and learning process of biology at PTM-Limited in class XI IPA SMAN 1 Pangkalan Kuras is 69.59% categorized as good.Key Words: Learning evaluation, Biology teaching and learning,Limited Face to face Learning.